Hormonal Regulation of Physiology, Innate Immunity and Antibody Response to H1N1 Influenza Virus Infection During Pregnancy - Littauer, Elizabeth Q.; Skountzou, Ioanna (Frontiers in Immunology, 2018)
In 2009, the H1N1 swine flu pandemic highlighted the vulnerability of pregnant women to influenza viral infection. Pregnant women infected with influenza A virus were at increased risk of hospitalization, severe acute respiratory distress syndrome (ARDS) associated with high mortality, while their newborns had an increased risk of pre-term birth or low birth weight. Pregnant women have a unique immunological profile modulated by the sex hormones required to maintain pregnancy, namely progesterone and estrogens. The role of these hormones in coordinating maternal immunotolerance in uterine tissue and cellular subsets has been well researched; however, these hormones have wide-ranging effects outside the uterus in modulating the immune response to disease. In this review, we compile research findings in the clinic and in animal models that elaborate on the unique features of H1N1 influenza A viral pathogenesis during pregnancy, the crosstalk between innate immune signaling and hormonal regulation during pregnancy, and the role of pregnancy hormones in modulating cellular responses to influenza A viral infection at mid-gestation. We highlight the ways in which lung architecture and function is stressed by pregnancy, increasing baseline inflammation prior to infection. We demonstrate that infection disrupts progesterone production and upregulates inflammatory mediators, such as cycloogenase-2 (COX-2) and prostaglandins, resulting in pre-term labor and spontaneous abortions. Lastly, we profile the ways in which pregnancy alters innate and adaptive cellular immune responses to H1N1 influenza viral infection, and the ways in which these protect fetal development at the expense of effective long-term immune memory. Thus, we highlight advancements in the field of reproductive immunology in response to viral infection and illustrate how that knowledge might be used to develop more effective post-infection therapies and vaccination strategies.